Extended-duration work shifts among care workers: a scoping review protocol - Yong Xu; Yuting Song; Lori E Weeks; Mengjiao Xu; Caifeng Lan; Xueying Liu; Sihan Dong (BMJ Open)
Introduction The available literature reviews of shift work among care workers are almost exclusively focused on 8-hour shifts and 12-hour shifts or 24-hour on-call shifts for physicians. We do not yet know the scope of evidence regarding extended-duration work shifts (defined as on-duty shifts of 16 or more hours per shift) in diverse healthcare settings, such as the impact on care workers and recipients of care. In this proposed scoping review, we aim to provide an overview of the current research regarding extended-duration work shifts among care workers in various healthcare settings.Methods and analysis We will conduct this scoping review in accordance with the Joanna Briggs Institute scoping review methodology. Comprehensive searches will be conducted in PubMed, Embase, MEDLINE, Web of Science and CINAHL (Cumulative Index to Nursing and Allied Health Literature) databases and grey literature sources. We will include empirical studies that focus on extended-duration work shifts among care workers working in different healthcare settings, including home care, community, acute care settings, long-term care homes and assisted living facilities. We will not apply language restrictions. We will conduct searches in August 2024, followed by screening of records. We will exclude research on on-call work shifts and investigations that solely focus on interns. The included literature will be screened independently by pairs of reviewers at the title and abstract review phase, followed by a full-text review for relevant literature. Any disagreement will be resolved by consensus or discussion with a third reviewer. The results will be extracted and summarised in the final report in tabular form, when possible, along with narrative synthesis.Ethics and dissemination All data for this study will come from published literature, so an ethics review is not necessary. The findings will be disseminated through conference presentations and publication in peer-reviewed journals, with the expectation that they will guide future research and inform future management of work shifts in care workers.